Applying sociolinguistics : domains and face-to-face interaction - Boxer, Diana, 1948- (Impact, studies in language and society, 2002)
Diana Boxer's Applying Sociolinguistics: Domains and Face-to-Face Interaction is an up-to-date overview of discourse studies in oral interaction. Its focus is on encounters in the various spheres of life: family, educational, social, religious, and work, with an additional chapter on cross-cultural face-to-face interaction in these domains. Each chapter reviews current research in that specific domain, with particular attention to methodological issues. For example, in-depth explanations are offered to the reader on how the various approaches to studying face-to-face discourse (e.g. ethnograph.